Red hat linux networking and system administration - Collings, Terry (Wiley, 2005)
Starts with the basics of Red Hat, the leading Linux distribution in the U.S., such as network planning and Red Hat installation and configuration. Offers a close look at the new Red Hat Enterprise Linux 4 and Fedora Core 4 releases. New chapters cover configuring a database server, creating a VNC server, monitoring performance, providing Web services, exploring SELinux security basics, and exploring desktops. Demonstrates how to maximize the use of Red Hat Network, upgrade and customize the kernel, install and upgrade software packages, and back up and restore the file system. The four CDs contain the full Fedora Core 4 distribution